How do e-book readers enhance learning opportunities for distance work-based learners? - Gabi Witthaus; Alejandro Armellini; Ming Nie; Kelly Barklamb (Association for Learning Technology, 2011)
We report on the incorporation of e-book readers into the delivery of two distance-taught master's programmes in Occupational Psychology (OP) and one in Education at the University of Leicester, UK. The programmes attract work-based practitioners in OP and Teaching English to Speakers of Other Languages, respectively. Challenges in curriculum delivery included the need for more flexibility in the curricula, better access to essential readings and maximising the benefit of learners' limited study time. As part of a suite of pilot changes to curriculum design and delivery, 28 Sony PRS-505™ e-book readers were pre-loaded with course materials and sent out to students. The evidence suggests that the students' learning experiences improved as a result of four key benefits afforded by the e-book readers: enhanced flexibility in curriculum delivery to accommodate the mobile lifestyle of our learners, improved efficiency in the use of study time, especially short breaks during the working day, new strategies for reading course materials and cost. We discuss the opportunities and limitations associated with the e-book readers used and the challenges encountered in the study.